KEBIJAKAN KEAMANAN DAN LUAR NEGERI BERSAMA UNI EROPA: STUDI KASUS â€œDUKUNGAN UNI EROPA TERHADAP UKRAINA DALAM MELAWAN GERAKAN SEPARATISME PRO- RUSIAâ€ - Radityo Wicaksono (HI 15 UMY 028, 2015)
*28 The aim of this research is to recognize the reason behind European Unionâ€™s support towards Ukraine in conflict between pro-Russia separatism movement and Ukraine government. This research explains European Union, commonly known as a regional organization, that gives contribution to resolve the separatism conflict which happened in Ukraine. European Union as a regional organization manage to administer its function in international peace keeping through one of its pillar called CFSP. However, up until now there is no sign that this conflict will end any time soon. Instead, the separatism movement is keep expanding its influence in South and East Ukraine.